2019
DOI: 10.3126/ije.v8i2.25506
|View full text |Cite
|
Sign up to set email alerts
|

Hygiene Practices and Airborne Microbial Concentrations in Restaurants

Abstract: This study was carried out to evaluate bioaerosol concentrations in the indoor air and the hygiene practices of restaurants to highlight the exposure risks and improve food safety in restaurants. Using depositional sampling techniques, air samples were collected from each restaurant kitchen and dining room and aerobically cultured. Hygiene/sanitary conditions were assessed using observation schedules and questionnaires. Meteorological parameters were also monitored during air sampling. The results revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…Bashar Haruna Gulumbe et al (2019) suggested that bioaerosol concentrations in the indoor air and the hygiene practices of restaurants increase the risk and improve food safety in restaurants. The findings showed that the indoor air quality was found to be poor, with the levels of airborne bacteria and fungi exhibiting levels higher than the prescribed limits.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Bashar Haruna Gulumbe et al (2019) suggested that bioaerosol concentrations in the indoor air and the hygiene practices of restaurants increase the risk and improve food safety in restaurants. The findings showed that the indoor air quality was found to be poor, with the levels of airborne bacteria and fungi exhibiting levels higher than the prescribed limits.…”
Section: Problem Statementmentioning
confidence: 99%
“…Recent studies have shown that consumers are becoming more health-conscious and prioritize good health and a nice environment over price (Bashar Haruna Gulumbe et al, 2019). However, the willingness of consumers to pay for premium foods is affected by various determinants such as gender, region, and age .…”
Section: Problem Statementmentioning
confidence: 99%